Phenolysis of 2, 2?-Biphenoxy Thiophosphinic Chloride: Crystal Structures and DFT Calculations of 2, 2?-Biphenyl 4-Tert-Butylphenyl Thiophosphinate and 2, 2?-Biphenyl 3,4-di-Methylphenyl Thiophosphinate - Begec, Saliha; Yüksel, Fatma; Chumakov, Yurii; Alatas, Sümeyya; Kilic, Adem (Taylor & Francis Ltd, 2023)
In this work, firstly, thiophosphoryl chloride, PSCl3 (1), with 2,2'-dihydroxybiphenyl, 2,2 '-HOC6H4C6H4OH (2) were reacted. 2, 2 '-biphenoxy thiophosphinic chloride (3) was obtained from this reaction. Second, the reactions of compound (3) with sterically hindered phenol derivatives (4a-4h) were investigated. Novel alkyl-substituted phenyl 2, 2 '-biphenyl-thiophosphinate esters (C6H4O)(2)P(S)OAr (5-12) were obtained from these reactions. Structures of (5-12) were defined by IR, H-1, C-13, P-31 NMR spectroscopy, and elemental analysis. The molecular structures of 2, 2 '-biphenyl 4-tert-butylphenyl thiophosphinate (11) and 2, 2 '-biphenyl 3,4-di-methylphenyl thiophosphinate (6) were determined by single-crystal X-ray diffraction. Density functional theory (DFT) calculations of compounds 6 and 11 were made. The theoretical analysis of IR and NMR spectra was performed by DFT based on B3LYP level of theory.
Keywords: Sterically hindered phenols; thiophosphoryl chloride; phosphorothionates; 2,2 '-dihydroxybiphenyl; X-ray crystal structure; DFT calculations